Phelan-McDermid syndrome in two adult brothers: atypical bipolar disorder as its psychopathological phenotype? - Verhoeven WMA (Dove Medical Press, 2012)
Willem MA Verhoeven1,2, Jos IM Egger1,3,4, Marjolein H Willemsen5, Gert JM de Leijer6, Tjitske Kleefstra51Vincent van Gogh Institute for Psychiatry, Centre of Excellence for Neuropsychiatry, Venray, 2Erasmus University Medical Centre, Department of Psychiatry, Rotterdam, 3Donders Centre for Cognition, Radboud University Nijmegen, Nijmegen, 4Behavioural Science Institute, Radboud University Nijmegen, Nijmegen, 5Department of Human Genetics, Radboud University Nijmegen Medical Centre, Nijmegen, 6Dichterbij, Institutes for Intellectual Disabilities, Gennep, The NetherlandsAbstract: The 22q13.3 deletion, or Phelan-McDermid syndrome, is characterized by global intellectual disability, generalized hypotonia, severely delayed or absent speech associated with features of autism spectrum disorder, and minor dysmorphisms. Its behavioral phenotype comprises sleep disturbances, communication deficits, and motor perseverations. Data on psychological dysfunctions are so far not available. Previous studies have suggested that the loss of one copy of the gene SH3 and multiple ankyrin repeat domains 3 (SHANK3) is related to the neurobehavioral phenotype. Additional genes proximal to SHANK3 are also likely to play a role in the phenotype of patients with larger deletions. The present paper describes two adult brothers with an identical 2.15 Mb 22qter (22q13.32q13.33) deletion, of whom the youngest was referred for evaluation of recurrent mood changes. In both patients, magnetic resonance imaging of the brain showed hypoplasia of the vermis cerebelli. Extensive clinical examinations led to a final diagnosis of atypical bipolar disorder, of which symptoms fully remitted during treatment with a mood stabilizer. In the older brother, a similar psychopathological picture appeared to be present, although less severe and with a later onset. It is concluded that the behavioral phenotype of the 22q13.3 deletion syndrome comprises absent or delayed speech and perseverations with associated autistic-like features, whereas its psychopathological phenotype comprises an atypical bipolar disorder. The latter may have implications for the treatment regime of the syndrome-related behavioral disturbances.Keywords: 22q13.3 deletion syndrome, 22qter, Phelan-McDermid, SHANK3, autism spectrum, unstable mood disorder, cerebellar vermis